HOST ROCK AND MINERALIZED ORES GEOCHEMISTRY OF BANTARHUNI VEIN, ARINEM DEPOSIT, WEST JAVA – INDONESIA - Yuningsih, Euis Tintin (Bulletin of Scientific Contribution, 2016)
There are closed spatial relationship between the different phases, the different metallic minerals, the precious-metals bearing minerals, the volcanic host rock and the plutonic intrusions of the Arinem vein system. Nine samples from Bantarhuni vein including four samples from quartz-sulfide vein from different stages and level, and five samples from altered host rock were analyzed geochemically by Induced Couple Plasma (ICP) and Induced Couple Plasma Mass Spectrometer (ICP-MS) to identified the geochemical characteristics of Bantarhuni vein system. The geochemical data obtained from the quartz-sulfide vein and altered host rock of the Bantarhuni vein is mostly similar to those obtained from Arinem vein samples. Some samples from the alteration zone have contents similar to the less altered Jampang Formation and andesitic Miocene and Pliocene intrusions rocks, with a little depletion and enrichment for some oxides. The abundance of ore and gangue minerals vary among each stage of mineralization of Bantarhuni vein. The REE in the Arinem and Bantarhuni veins considered to have been extracted by water/rock interaction between hydrothermal solution and country rocks. Some REE pattern of the mineralized Bantarhuni vein show irregularly pattern and this is could be due to high content of sulfide minerals in the samples, or due to analytical error during sample dissolution. The gold and silver contents in the Arinem and Bantarhuni veins vary very much and there is relatively low Au and Ag concentrations occur in samples from any alteration zone. There is no correlation found between gold and other major ore elements except for Ag. The highest content of Au is having low ΣREE.   Keywords : Bantarhuni vein, Geochemical, quartz-sulfide vein, water-rock interaction.                                            Terdapat hubungan spasial antara fase yang berbeda, mineral logam yang berbeda, mineral yang mengandung logam mulia, batuan induk (host rock) vulkanik dan intrusi plutonik dalam sistem urat Arinem. Sembilan sampel dari urat Bantarhuni yang terdiri dari empat sampel dari urat kuarsa-sulfida dari stages dan kedalaman yang berbeda, dan lima sampel dari host rock yang terubah dianalisis secara geokimia degan Induced Couple Plasma (ICP) dan Induced Couple Plasma Mass Spectrometer (ICP-MS) untuk mengidentifikasi karakteristik geokimia dari sistem urat Bantarhuni. Data analisis geokimia yang diperoleh dari urat kuarsa-sulfida dan batuan induk terubah dari urat Bantarhuni sebagian besar sama dengan yang diperoleh dari sampel urat Arinem. Beberapa sampel dari zona alterasi memiliki kandungan mirip dengan Formasi Jampang yang terubah lemah dan batuan intrusi andesit berumur Miosen dan Pliosen, dicirikan dengan sedikit pengurangan dan pengayaan untuk beberapa oksida. Kelimpahan bijih dan mineral gang bervariasi di dalam setiap tahap mineralisasi di urat Bantarhuni. REE di urat Arinem dan Bantarhuni kemungkinan diekstraksi dengan adanya interaksi air/batuan antara fluida hidrothermal dan batuan sampingnya. Beberapa pola REE dari urat Bantarhuni yang termineralisasi menunjukkan pola yang tidak teratur dan hal ini kemungkinan disebabkan oleh tingginya kandungan mineral sulfida dalam sampel, atau karena kesalahan pada saat analisis dalam pelarutan sampel. Kandungan emas dan perak dalam urat Arinem dan Bantarhuni sangat bervariasi dan konsentrasi Au dan Ag pada sampel dari setiap zona alterasi relatif rendah. Tidak ada korelasi ditemukan antara emas dan unsur bijih utama lainnya kecuali dengan Ag. Sampel dengan kandungan Au tertinggi adalah sampel yang memiliki ΣREE rendah. Kata kunci: Urat Bantarhuni, geokimia, urat kuarsa-sulfida, interaksi air-batuan.